Fluororesin film, and method of manufacturing the same

The development of a tetrafluoroethylene polymer film with controlled thickness, haze, and thermal expansion, produced via a T-die casting method, addresses the challenges of dimensional stability and transparency in flexible printed wiring boards, achieving effective performance in high-frequency applications.

JP2025063322AActive Publication Date: 2025-04-15AGC INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2025011681
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2025-01-27
Publication Date
2025-04-15
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Tetrafluoroethylene polymer films suffer from poor dimensional stability, high haze, and difficulty in achieving both transparency and heat resistance, especially when thickened for use in flexible printed wiring boards.

Method used

An extrusion molded film made of a tetrafluoroethylene polymer with specific composition and processing conditions, including a thickness of 100-200 μm, haze of 8% or less, and a thermal expansion rate of -1-+1% in both flow and width directions, achieved through a T-die casting method with controlled cooling conditions.

Benefits of technology

The resulting film exhibits good dimensional stability, low haze, and excellent yield in circuit formation, while maintaining transparency and heat resistance, making it suitable for use as a substrate in high-frequency applications such as antenna substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063322000001_ABST
    Figure 2025063322000001_ABST
Patent Text Reader

Abstract

To provide a film having good dimensional stability, low haze, good yield rate in circuit formation, and capable of achieving both transparency and heat resistance, and a method of manufacturing the same.SOLUTION: A film made of tetrafluoroethylene-based polymer has a thickness of 100 to 200 μm, a haze of 8% or less, a thermal shrinkage rate after 30 minutes heating at 180°C both in the flow direction and the width direction of -1% or more and +1% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tetrafluoroethylene polymer film and a method for producing the same. [Background technology]

[0002] As electronic devices become lighter and more compact, flexible printed circuit boards (FPCs) are widely used as a lightweight and flexible wiring material to address the amount of wiring and space limitations within the devices. In recent years, the speed of signals transmitted on printed circuit boards has increased, leading to higher frequencies. Accordingly, there is a strong demand for FPCs to have low dielectric properties (low dielectric constant, low dielectric loss tangent) in the high frequency range. In response to this demand, substrate films made of low dielectric properties such as liquid crystal polymers (LCPs), syndiotactic polystyrene (SPS), and polyphenylene sulfide (PPS) have been proposed as substrate films for FPCs, instead of conventional polyimide (PI) and polyethylene terephthalate (PET). On the other hand, with the pursuit of improved design for electronic devices, opportunities for FPCs to be used in places where they are visible to the public are increasing, such as flexible devices such as flexible displays and touch panels, and electronic devices that use semiconductor elements such as LEDs by reflow. In such electronic devices, FPCs need to be transparent.

[0003] PI film has excellent heat resistance, but transparency is an issue. PET film has excellent transparency but low heat resistance, and when used in flexible printed wiring boards, issues include warping of the substrate and dimensional changes due to heat during reflow. Tetrafluoroethylene polymers such as polytetrafluoroethylene (PTFE) have high transparency and excellent physical properties such as chemical resistance, water and oil repellency, heat resistance, and electrical properties, and have a low dielectric constant and low dielectric dissipation factor compared to materials such as PI, LCP, SPS, and PPS, so they can be used as a transparent and reflow-resistant substrate film for FPCs. On the other hand, tetrafluoroethylene polymers have poor dimensional stability and are prone to misalignment during circuit processing. For this reason, Patent Document 1 proposes a method of removing the distortion by annealing the film after it has been formed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 203243 Summary of the Invention [Problem to be solved by the invention]

[0005] Tetrafluoroethylene polymers have crystallinity, and the crystals tend to grow during the cooling process of the molten molded product, so the resulting film tends to have a large haze even if it has a high light transmittance. In addition, when the film becomes thick, it is difficult to eliminate distortion even by heat treatment as in the method of Patent Document 1, and the film has poor dimensional stability, so that the flatness of the film may be impaired by heat treatment.

[0006] As a result of extensive investigations, the present inventors have found a film that has good dimensional stability, low haze, good yield in circuit formation, and is capable of achieving both transparency and heat resistance. It is an object of the present invention to provide a film having the above characteristics and a method for producing the same. [Means for solving the problem]

[0007] The present invention has the following aspects. <1> An extrusion-molded film made of a tetrafluoroethylene-based polymer, the film having a thickness of 100 to 200 μm, a haze of 8% or less, and a thermal expansion rate of -1 to +1% in both the machine direction and width direction of the film after heating at 180°C for 30 minutes. <2> The tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether). <1> of film. <3> The tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether) and having a polar functional group, or a tetrafluoroethylene-based polymer containing 2.0 to 5.0 mol % of units based on perfluoro(alkyl vinyl ether) based on all units and having no polar functional group. <1> or <2> of film. <4> The melting temperature of the tetrafluoroethylene polymer is 260 to 320°C. <1> ~ <3> Any of the films.

[0008] <5> The above <1> ~ <4> The method for producing any one of the films described above by a T-die casting method includes a step of discharging the tetrafluoroethylene-based polymer in a molten state from a die to be extruded, and then sandwiching the film between two temperature-controlled rolls to cool it. <6> The temperature of the two temperature-controlled rolls is 150 to 250°C for one roll and 80 to 150°C for the other roll. <5> Manufacturing method. <7> The method includes an extrusion molding apparatus having a kneading section and a hopper connected to the kneading section, and when pellets of a tetrafluoroethylene-based polymer having a melting temperature of 260 to 320°C are charged into the hopper and a molten kneaded product melted and kneaded in the kneading section is discharged from a T-die to produce a film, the method further includes an operation of adjusting the temperature of the pellets at a connecting portion of the hopper with the kneading section to a range of (the melting temperature - 200) to (the melting temperature - 100)°C, and then supplying the pellets to the kneading section. <5> or <6> Manufacturing method. <8> The diameter of the pellet is 1.0 to 4.0 mm. <5> ~ <7> A manufacturing method of any one of the above.

[0009] <9> The hopper is a multi-stage hopper having a first stage and a second stage arranged on the kneading section side of the first stage, <5> ~ <8> A manufacturing method of any one of the above. <10> The pressure in the step closest to the kneading section of the hopper is 1000 Pa or less. <5> ~ <9> A manufacturing method of any one of the above. <11> The extrusion molding apparatus includes a T-die connected to the axial side of the kneading section opposite to the hopper, and a static mixer provided between the kneading section and the T-die. <5> ~ <10> A manufacturing method of any one of the above. <12> The tetrafluoroethylene-based polymer is discharged in a molten state from a T-die, and the molten tetrafluoroethylene-based polymer is heated in a non-contact heating section before contacting the polymer with a first cooling roll. <5> ~ <11> A manufacturing method of any one of the above. <13> The difference between the temperature of the tetrafluoroethylene-based polymer in the T-die and the temperature of the first cooling roll is 250° C. or less. <12> Manufacturing method. <14> The absolute value of the difference between the temperature of the tetrafluoroethylene-based polymer in the T-die and the temperature of the non-contact heating part is 70 ° C. or less. <12> or <13> Manufacturing method.

[0010] <15> The above <1> ~ <4> and a substrate layer made of a substrate other than the above-mentioned film. Effect of the Invention

[0011] According to the present invention, a film having good dimensional stability, low haze, good yield in circuit formation, and both transparency and heat resistance and a method for producing the same are provided. According to the present invention, a thick film having a thickness of about 100 μm, which is particularly preferred as a base material for an antenna substrate, can be provided. The film of the present invention is useful as a colorless, transparent, low-loss antenna substrate. [Brief description of the drawings]

[0012] [Figure 1]FIG. 1 is a schematic diagram showing one embodiment of a film production apparatus used in Method 1. [Diagram 2] FIG. 1 is a schematic diagram illustrating one embodiment of an extrusion apparatus that may be used in the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing one embodiment of a film production apparatus used in Method 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The following terms have the following meanings. The "film thickness" is the average value of the measurements taken at 10 equally spaced points across the width of the film using a contact thickness meter DG-525H (manufactured by Ono Sokki Co., Ltd.) with a probe AA-026 (Φ10 mm, SR7). The "melting temperature of a polymer" is the temperature corresponding to the maximum of the melting peak as measured by differential scanning calorimetry (DSC). The term "unit" in a polymer means an atomic group based on one molecule of a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit." The "glass transition point of a polymer" is a value measured by analyzing a polymer using a dynamic mechanical analysis (DMA) method.

[0014] The film of the present invention is an extrusion molded film made of a tetrafluoroethylene polymer (hereinafter also referred to as "F polymer"), has a thickness of 100 to 200 μm, a haze of 8% or less, and a thermal expansion rate after heating at 180° C. for 30 minutes of -1 to +1% in both the machine direction (hereinafter referred to as MD) and width direction (hereinafter referred to as TD) of the film. The film of the present invention may be a roll film in a wound state. As the laminate of the present invention having a layer made of the film of the present invention and a base layer made of a base material other than the film of the present invention, a laminate made of the film of the present invention and a metal foil is preferred. If the laminate made of the film of the present invention and a metal foil is cut to a predetermined length and the metal foil is processed into a transmission circuit (including vias), it can be suitably used as an FPC, for example, as an antenna substrate that is colorless, transparent, and excellent in electrical properties. The layer made of the film of the present invention is hereinafter referred to as "F polymer layer", and a base layer made of a base material other than the film of the present invention is hereinafter simply referred to as "base layer" unless otherwise specified.

[0015] In a typical film of a heat-meltable fluororesin, molding distortions remain due to the manufacturing method (melt molding method by extrusion molding). In the film of the present invention, by appropriately controlling the cooling conditions of the resin film during molding as described below, the thermal expansion rate of both MD and TD is -1 to +1%, the distortion in each direction is small and sufficiently uniform, and the film has excellent dimensional stability, and even if the thickness is 100 to 200 μm, the haze is 8% or less, and the film has excellent transparency. Therefore, even in the laminate having such a film layer, the distortion is small and sufficiently uniform, so that it is considered to have excellent thermal shock resistance, suppressed deformation, and excellent dimensional stability. For example, the laminate of the present invention having a metal foil as a base layer has high thermal shock resistance when forming through holes or vias in processing it into a printed wiring board, and as a result, a printed wiring board that is less likely to break is easily obtained.

[0016] The thermal expansion rate of the film is measured as follows. First, a square test piece with 12 cm sides and two sides along the MD and two sides along the TD is cut out from the film. Next, a line segment with a length of 10 cm is drawn in the MD and TD on the surface of the obtained test piece. Next, the test piece is heated in an oven at 180°C for 30 minutes, then removed and naturally cooled to 25°C, and the length of the line segment is measured again. The thermal expansion rate is a value calculated according to the formula: {(length of the line segment before heating)-(length of the line segment after heating)} / (length of the line segment before heating) x 100. In other words, the thermal expansion rate is the rate of change (percentage) in the length of the line segment before and after heating. Note that a negative value indicates an expansion of the film, and a positive value indicates a contraction of the film. The thermal expansion rate of the film of the present invention is -1 to +1% in both MD and TD of the film, preferably -0.8 to +0.8%, and more preferably -0.5 to +0.5%. If the thermal expansion rate is within the above range, wrinkles due to distortion of the film are less likely to occur even when heated.

[0017] The F polymer in the present invention is a polymer containing units based on tetrafluoroethylene (TFE) (TFE units). The F polymer in the present invention is heat-meltable, and its melting temperature is preferably 260 to 320° C., more preferably 275 to 315° C., and even more preferably 290 to 310° C. In this case, the moldability of the F polymer and the mechanical strength of the film of the present invention are easily balanced. The glass transition point of the F polymer is preferably from 75 to 125°C, more preferably from 80 to 100°C.

[0018] Examples of F polymers include polytetrafluoroethylene (PTFE), polymers (PFA) containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units), and polymers (FEP) containing units based on hexafluoropropene (HFP), with PFA being preferred. Preferred PAVEs are CF2=CFOCF3, CF2=CFOCF2CF3, and CF2=CFOCF2CF2CF3 (PPVE), with PPVE being more preferred.

[0019] The F polymer preferably has a polar functional group. The polar functional group may be contained in a unit in the F polymer, or may be contained in a terminal group of the main chain of the F polymer. Examples of the latter embodiment include an F polymer having a polar functional group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer having a polar functional group obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. As the polar functional group, a hydroxyl group-containing group and a carbonyl group-containing group are preferred. As the hydroxyl group-containing group, a group containing an alcoholic hydroxyl group is preferred, and -CF2CH2OH and -C(CF3)2OH are more preferred. The carbonyl group-containing group is a group that contains a carbonyl group (>C(O)). Preferred examples of the carbonyl group-containing group include a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) and a carbonate group (-OC(O)O-), and more preferred are acid anhydride residues.

[0020] When the F polymer has a carbonyl group-containing group, the number of carbonyl group-containing groups in the F polymer is 1×10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000, and further preferably 800 to 1500. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.

[0021] As the F polymer, preferred are polymer (1) having a polar functional group containing TFE units and PAVE units, and polymer (2) having no polar functional group containing TFE units and PAVE units and containing 2.0 to 5.0 mol % of PAVE units based on all units. These F polymers tend to form microspherulites in molded products, which increases adhesion to other components. As a result, molded products with excellent surface smoothness, adhesion, and electrical properties are more likely to be obtained.

[0022] The polymer (1) is preferably a polymer containing a TFE unit, a PAVE unit, and a unit based on a monomer having a polar functional group, and more preferably a polymer containing these units in the following order of 90 to 99 mol%, 0.5 to 9.97 mol%, and 0.01 to 3 mol% relative to the total units. In addition, as the monomer having a polar functional group, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"). Specific examples of the polymer (1) include polymers described in International Publication No. 2018 / 16644.

[0023] Polymer (2) is composed of only TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol% of TFE units and 2.0 to 5.0 mol% of PAVE units based on all units. The content of PAVE units in polymer (2) is preferably 2.1 to 5.0 mol%, more preferably 2.2 to 5.0 mol%, based on all units. In addition, the polymer (2) having no polar functional group means that the number of carbon atoms constituting the polymer main chain is 1×10 6 This means that the number of polar functional groups in the polymer is less than 500 per unit. The number of the polar functional groups is preferably 100 or less, more preferably less than 50. The lower limit of the number of the polar functional groups is usually 0. The polymer (2) may be produced by using a polymerization initiator or a chain transfer agent that does not generate a polar functional group as a terminal group of the polymer chain, or by fluorinating an F polymer having a polar functional group (such as an F polymer having a polar functional group derived from a polymerization initiator at the terminal group of the main chain of the polymer). As a method of fluorination treatment, a method using fluorine gas (see JP 2019-194314 A, etc.) can be mentioned.

[0024] The film of the present invention may contain other resins besides the F polymer. However, the content of the F polymer contained in the film is preferably 80% by mass or more, more preferably 100% by mass. Examples of other resins besides the F polymer include epoxy resins, polyimide resins, polyamic acids which are polyimide precursors, acrylic resins, phenolic resins, liquid crystal polyester resins, polyolefin resins, modified polyphenylene ether resins, polyfunctional cyanate ester resins, polyfunctional maleimide-cyanate ester resins, polyfunctional maleimide resins, vinyl ester resins, urea resins, diallyl phthalate resins, melamine resins, guanamine resins, melamine-urea co-condensation resins, styrene resins, polycarbonate resins, polyarylate resins, polysulfones, polyarylsulfones, aromatic polyamide resins, aromatic polyetheramides, polyphenylene sulfides, polyaryl ether ketones, polyamideimides, and polyphenylene ethers.

[0025] The film of the present invention may further contain, for example, an inorganic filler, an organic filler, a thixotropic agent, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a brightening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a viscosity adjusting agent, a flame retardant, and the like.

[0026] As the inorganic filler, boron nitride filler, beryllia filler (beryllium oxide filler), silicate filler (silica filler, wollastonite filler, talc filler), and metal oxide (cerium oxide, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, etc.) filler are preferable. In addition, the inorganic filler may be surface-treated at least partially. Examples of the surface treatment agent used for such surface treatment include polyhydric alcohol, saturated fatty acid, its ester, amine, paraffin wax, silane coupling agent, silicone, and polysiloxane. The shape of the inorganic filler may be any of granular, needle-like (fibrous), plate-like, etc., and specific shapes include spherical, scale-like, layered, leaf-like, apricot-like, columnar, cockscomb-like, equiaxed, leaf-like, micaceous, block-like, flat, wedge-like, rosette-like, net-like, and prismatic shapes.

[0027] The method for producing the film of the present invention will be described below. From the viewpoint of being able to adjust the distortion of the film, the film of the present invention can be suitably produced by a T-die casting method (a melt extrusion method using a T-die). The present inventors have found that the MD and TD distortions of a film produced by the T-die casting method depend on the state (temperature, fluidity) of the molten F polymer and the cooling conditions, and are determined by the state of the molten F polymer extruded from the T-die until it is crystallized by a cooling roll. In other words, the present inventors have found that if the state of the F polymer and the cooling conditions are appropriately set to control the crystallization of the F polymer, the MD and TD heat shrinkage rates (distortions) of the obtained film converge to a predetermined range, and low haze can be achieved even in a relatively thick film of 100 to 200 μm due to the suppression of crystal growth.

[0028] The film manufacturing method of the present invention includes the steps of discharging the F polymer in a molten state from a T-die to perform extrusion molding, and then sandwiching and cooling the film between two temperature-controlled rolls (Method 1). Preferably, one of the two temperature-controlled rolls has a temperature of 150 to 250°C, and the other has a temperature of 80 to 150°C. More preferably, one of the two temperature-controlled rolls is a metal roll controlled to 150 to 250°C, and the other is a metal elastic roll controlled to 80 to 150°C.

[0029] Fig. 1 is a schematic diagram showing one embodiment of a film production apparatus used in Method 1. The production apparatus 10 shown in Fig. 1 has a T-die 20, a first cooling roll (initial cooling roll) 30 arranged vertically below the T-die 20, a quenching roll 301, a second cooling roll 40 arranged alongside the first cooling roll 30, a take-up roll 50 that takes up the film 1, and transport rolls 61 and 62 arranged between the take-up roll 50 and the second cooling roll 40. The first cooling roll 30 may further be equipped with an air knife 70, and preferably is equipped with it.

[0030] The F polymer is melted by heating in an extruder (not shown) connected to the T-die 20 and fed into the T-die 20. The molten F polymer is discharged from the lip 21 of the T-die 20 toward the first cooling roll 30. The discharged molten F polymer then comes into contact with the first cooling roll 30 and is cooled by being pinched between the first cooling roll 30 and the quenching roll 301. Furthermore, the F polymer passes through the second cooling roll 40 and is transported by the transport rollers 61 and 62. Thereafter, the F polymer is taken up as the film 1 on the take-up roll 50. As the first cooling roll 30, it is preferable to use a metal roll capable of controlling the temperature, and as the quenching roll 301, it is preferable to use an elastic metal roll.

[0031] The elastic metal roll may be a roll whose surface is made of a metal material such as stainless steel, and whose space between the metal surface material and the shaft roll is filled with an elastic material such as a fluid or rubber. The elastic metal roll may, for example, be made up of a substantially cylindrical shaft roll that is rotatable, a cylindrical metal thin film that is arranged to cover the outer circumferential surface of the shaft roll and contacts the film-like material, and a fluid sealed between the shaft roll and the metal thin film. The elastic metal roll exhibits elasticity due to the fluid, and has the characteristic of being capable of roll compression molding at a low linear pressure. In the present invention, this characteristic is utilized to contribute to the control of film cooling conditions. The material of the shaft roll can be stainless steel. The metal thin film is preferably made of stainless steel and has a thickness of 2 to 5 mm. The metal thin film is preferably bendable or flexible, and preferably has a seamless structure without a welded joint. A metal elastic roll having such a metal thin film is excellent in durability, and can be handled in the same way as a normal mirror roll if the metal thin film is mirror-finished. From the viewpoint of obtaining a film with excellent surface smoothness, it is more preferable that the surface of the metal elastic roll is a mirror roll. Examples of commercially available metal elastic rolls include the UF roll from Hitachi Zosen Corporation and the SF roll from Chiba Machinery Industry Co., Ltd.

[0032] The molten F polymer is cooled by being sandwiched between the quenching roll 301, which is preferably a metallic elastic roll, and the first cooling roll 30, which is preferably a metallic roll, thereby rapidly cooling the film, suppressing crystal growth and reducing haze, and also reducing the accumulation of strain on the film sandwiched between the first cooling roll and the quenching roll. The temperature of the first cooling roll 30 is preferably 150 to 250°C, and the temperature of the quenching roll 301 is preferably 80 to 150°C from the viewpoint of being able to cool the film rapidly. Both the first cooling roll and the quenching roll are preferably configured to have a mechanism for passing a heat medium, and preferably have a dual mechanism for repeatedly passing the heat medium back and forth in the axial direction. The temperature of the first cooling roll and the temperature of the quenching roll both refer to the temperature of the heat medium. When the quenching roll is a metallic elastic roll, the temperature is preferably in a range that does not impair the characteristics of the metallic elastic roll itself.

[0033] In method 1, it is preferable to further provide an air knife 70 at a position immediately after the molten F polymer is sandwiched between the first cooling roll 30 and the quenching roll 301. The air knife 70 has the role of cooling the molten F polymer and pressing it against the first cooling roll 30 by uniformly blowing a slit-shaped air flow from a slit nozzle in a line in the width direction of the first cooling roll 30 on the line where the molten F polymer contacts the first cooling roll 30. Like the quenching roll 301, it has the effect of increasing the cooling efficiency of the F polymer, suppressing the haze of the obtained film, and reducing the thermal expansion and contraction rate. The temperature of the air blown out from the air knife is preferably 150 to 200° C., more preferably 170 to 200° C. If it is 150° C. or higher, the thermal expansion rate of the film is small, and if it is 200° C. or lower, the haze tends to be small. The flow velocity of the air blown out from the air knife is preferably 10 to 20 m / sec.

[0034] The film production method of the present invention further includes, in addition to Method 1, a method in which a film is produced from pellets of an F polymer having a melting temperature of 260 to 320° C. using, for example, an extrusion molding apparatus 11 shown in FIG. 2 (Method 2). Fig. 2 is a conceptual diagram showing one embodiment of an extrusion molding device used in Method 2. In the following description, the right side in Fig. 2 (forward in the transport direction of the molten kneaded material) is referred to as the "front end" and the left side (rear in the transport direction) is referred to as the "base end."

[0035] The extrusion molding apparatus 11 shown in Fig. 2 includes a hopper 2 and a kneading section 3 communicating with the hopper 2. The kneading section 3 in this embodiment is configured with a single-screw kneader having a cylinder 31 and one screw 32 rotatably provided within the cylinder 31. Use of a single-screw kneader makes it easier to prevent the F polymer from deteriorating when the pellets are melt-kneaded. In this case, when the total length of the screw 32 is L (mm) and the diameter is D (mm), the effective length (L / D) expressed as the ratio of the total length L to the diameter D is more preferably 30 to 45. If the effective length is within the above range, sufficient shear stress can be applied to the F polymer while preventing deterioration of the F polymer, and temperature unevenness of the molten kneaded product can be easily reduced.

[0036] A gear box 33 and a motor 34 are arranged in this order on the base end side of the cylinder 31. A gear (not shown) is connected to the tip of a rotating shaft 341 of the motor 34, and this gear meshes with a predetermined gear (not shown) in the gear box 33. In the gear box 33, the rotational motion of the rotating shaft 341 is accelerated or decelerated and transmitted to the rotating shaft 331. The tip end of the rotating shaft 331 is connected to the base end side of the screw 32. With this configuration, the rotation of the motor 34 is transmitted to the screw 32 to rotate the screw 32 at a predetermined rotation speed. As a result, the molten kneaded material is transported from the base end side (left side) to the tip end side (right side) in FIG.

[0037] In addition, a heater 35 is provided on the outer periphery of the cylinder 31. The pellets (F polymer) supplied into the cylinder 31 are melted by heating from the heater 35, mixed (kneaded) by the rotation of the screw 32, and transported toward the tip side. As a result, the pellets are melted and kneaded, and the molten and kneaded product is extruded from the tip opening 311 of the cylinder 31. A T-die 5 is disposed at the tip side of the cylinder 31 (the side opposite to the hopper 2 in the axial direction of the kneading section 3). The molten mixture extruded from the tip opening 311 of the cylinder 31 is discharged from the lower end opening (discharge port) of the T-die 5, and thereafter, as described in the present method 1, an F polymer film is produced. Here, the T-die 5 in FIG. 2 may be understood to correspond to the T-die 20 in FIG. 1 (or FIG. 3 described later). Although not shown, the T-die 5 is also provided with a heater.

[0038] In this embodiment, a static mixer 6 is provided between the cylinder 31 (kneading section 3) and the T-die 5. This static mixer 6 is an element that divides, converts, or reverses the flow path of the molten kneaded material to stir the molten kneaded material. By providing such a static mixer 6, it is not necessary to apply unnecessary external force to the molten and kneaded material, so that the molten and kneaded material can be uniformly kneaded while suppressing deterioration of the molten and kneaded material.

[0039] A hopper 2 is disposed on the base end side of the cylinder 31. The hopper 2 in this embodiment is configured as a two-stage hopper including a funnel-shaped first stage 21 and a funnel-shaped second stage 22 disposed closer to the kneading section 3 (cylinder 31) side than the first stage 21. A heater 211 and a pump P1 are connected to the first stage 21. This allows the pellets supplied into the first stage 21 to be heated under reduced pressure. The first step 21 is connected to the second step 22 via a connection portion 212 . A heater 221 and a pump P2 are connected to the second stage 22. This allows the pellets supplied into the second stage 22 to be heated under reduced pressure. The second step 22 is connected to the cylinder 31 via a connection portion 222 . The inner surface (inner peripheral surface) of the hopper 2 (first stage 21 and second stage 22) is preferably covered with a resin film. That is, the inner surface of the hopper 2 is preferably lined with a resin. This can sufficiently prevent the softened pellets from adhering to the inner surface of the hopper 2. The resin film can be made of a fluororesin such as PTFE.

[0040] The pellets used in the present method 2 may contain components other than the F polymer, but the content of the F polymer is preferably 80% by mass or more, and more preferably 100% by mass. Examples of the components other than the F polymer include the above-mentioned other resins and additives. The shape of the pellets may be spherical or cylindrical, with cylindrical being preferred. The diameter of the pellets is preferably 1.0 to 4.0 mm. Pellets with such a diameter can be heated (warmed) sufficiently to the inside when heated in the hopper 2 while preventing bridging (clogging) in the hopper 2.

[0041] In the present method 2, pellets of F polymer are preheated in the hopper 2, then fed to the kneading section 3, and the melt-kneaded mixture melted and kneaded in the kneading section 3 is discharged from the T-die 5 to produce a film. At this time, the temperature of the pellets at the connecting section 222 of the hopper 2 with the kneading section 3 is adjusted to the range of (X-200) to (X-100) ° C., where X is the melting temperature of the F polymer. The temperature of the pellets at the connecting section 222 of the hopper 2 with the kneading section 3 is preferably (X-175) to (X-125) ° C. Specifically, the pellet temperature is preferably 70 to 225 ° C., more preferably 105 to 195 ° C. In this case, bridging in the hopper 2 due to softening of the pellets is unlikely to occur. In addition, since the temperature unevenness of the melt-kneaded mixture in the kneading section 3 is sufficiently reduced, a film having a uniform thickness and preventing the occurrence of fish eyes is easily obtained.

[0042] The pressure in the second stage 22 (the stage closest to the kneading section 3) is preferably lower than the pressure in the first stage 21, and is preferably 1000 Pa or less, and more preferably 100 Pa or less. This makes it possible to sufficiently remove air from within the pellets, preventing the formation of a heat insulating layer due to air, and making it easy to prevent temperature unevenness from occurring in the molten kneaded material in the kneading section 3. The softened pellets are supplied to the kneading section 3. The rotation speed of the screw 32 is preferably 10 to 50 ppm. The heating temperature by the heater 35 is more preferably (X+30) to (X+50)°C. Melting and kneading the pellets under the above conditions makes it easier to form a homogeneous melt-kneaded product with little temperature variation, and as a result, makes it easier to obtain the film of the present invention. The molten mixture is supplied to a T-die 5 via a static mixer 6 and discharged from the T-die 5. The molten mixture discharged from the T-die 5 is formed into a film as described in the method 1, and taken up on a take-up roll. Furthermore, the extrusion molding device 11 may have a cutter as necessary.

[0043] According to this method 2, the surging phenomenon is highly suppressed, and the polymer is uniformly melted and kneaded without excessive heat history to form a film. Therefore, it is easy to produce a wide film with few defects (fisheyes) and sufficient length in the short direction. The number of fish eyes in the film of the present invention is 2 The lower limit of the number of fisheyes is preferably 0.

[0044] The film manufacturing method of the present invention further includes a method in which, in the method 1 or method 2, the F polymer is extruded in a molten state from a T-die and the molten F polymer is heated in a non-contact heating section before contacting the first cooling roll (method 3). Fig. 3 is a schematic diagram showing one embodiment of a film production apparatus used in the present method 3. The production apparatus 101 shown in Fig. 3 is similar to the production apparatus 10 in the present method 1, except that the production apparatus 10 further includes a pair of heaters (non-contact heating units) 80 disposed opposite each other between the T-die 20 and the first cooling roll 30.

[0045] The F polymer is melted by heating in an extruder (not shown) connected to the T-die 20 and fed into the T-die 20. The molten F polymer is discharged from the lip 21 of the T-die 20 toward the first cooling roll 30. Next, the discharged molten F polymer is heated without contacting the heater 80 when passing between a pair of heaters 80, contacts the first cooling roll 30, and is pressed against the first cooling roll 30 by the quenching roll 301 to be cooled. At this time, the molten F polymer may be cooled and pressed against the first cooling roll 30 by blowing a slit-shaped air flow uniformly in a line in the width direction of the first cooling roll 30 by an air knife 70 installed perpendicular to the tangent line to the first cooling roll 30. Furthermore, after passing through the second cooling roll 40, the F polymer is transported by the transport rollers 61 and 62 and taken up as the film 1 on the take-up roll 50.

[0046] According to this configuration, the molten F polymer discharged from the T-die 20 is maintained at a high temperature by heating with the heater 80 even while reaching the first cooling roll 30. Therefore, the molten F polymer flowing down toward the first cooling roll 30 maintains a relatively high fluidity, and is unlikely to be stretched due to its own weight or the tensile force of the first cooling roll 30. As a result, it is presumed that the occurrence of the bowing phenomenon (orientation of the F polymer in MD and TD) is suppressed when the molten F polymer is made into a film, and a film with small MD and TD distortion (thermal expansion and contraction rate) as described above can be obtained.

[0047] 3, the F polymer discharged from the T-die 20 is heated by the heater 80 from both sides in the thickness direction, so that the temperature uniformity in the thickness direction is high, and the effect of suppressing the occurrence of the bowing phenomenon is excellent. From the viewpoint of further improving the effect of suppressing the occurrence of the bowing phenomenon, it is preferable to configure the heater 80 so that the temperature of the F polymer in the width direction can be made uniform. In this case, for example, the width of the heater 80 may be designed to be sufficiently larger than the length of the F polymer in the width direction.

[0048] The temperature of F polymer in T die 20 is X 1 [℃], and the temperature of heater 80 is Z 1 [℃], the absolute value of the difference (|X 1 -Z 1 |) is preferably 70° C. or less, more preferably 30 to 50° C. In this case, the temperature of the F polymer can be kept sufficiently high until it reaches the first cooling roll 30 while preventing deterioration of the F polymer. In addition, when the die temperature and the die lip temperature are different, X 1 means the die temperature. The temperature of the first cooling roll 30 is set to Y 1 When [℃] is specified, the difference (X 1 -Y 1 ) is preferably 250° C. or less, more preferably 200° C. or less, and even more preferably 125 to 175° C. In this case, the degree of cooling of the F polymer by the first cooling roll 30 becomes more appropriate, so that distortions in the MD and TD are less likely to remain in the obtained film 1, and deformation due to insufficient cooling can also be suitably prevented. 1 The heating temperature is preferably 150 to 250°C.

[0049] In order to further improve the effect of suppressing the occurrence of the bowing phenomenon during cooling by the first cooling roll 30, it is preferable to configure the first cooling roll 30 so that the temperatures of the F polymer in the MD and TD can be made uniform. Therefore, the first cooling roll 30 is preferably configured to have a mechanism for passing a heat medium, and is preferably configured to have a dual mechanism for repeatedly passing the heat medium back and forth in the axial direction. 1 means the temperature of the heat transfer medium.

[0050] 3, a pair of heaters 80 are provided, but only one may be provided. Also, the non-contact heating unit may be configured with a blower device that blows hot air instead of the heater 80.

[0051] In all of Methods 1 to 3, the thickness (thickness t in Figs. 1 and 3) of the F polymer in a molten state before contacting the first cooling roll 30 is preferably 100 to 200 µm. In this case, the accuracy of heating by the heater 80 and cooling by the first cooling roll 30 is improved, and the resulting film 1 is less likely to have residual distortion in the MD and TD.

[0052] If the ratio of the opening of the lip 21 of the T-die 20 to the thickness of the final film 1 (draw ratio) is large, the molecular chains of the polymer contained in the F polymer are strongly stretched, and the polymer molecules tend to be oriented. As a result, the MD and TD distortions remaining in the film 1 tend to be large. Therefore, the draw ratio is preferably 50 or less. The peripheral speed of the first cooling roll 30 (peripheral speed S in Figs. 1 and 3) is more preferably 2 to 20 m / min from the viewpoint of further reducing the MD and TD distortions remaining in the film 1. The temperature of the second cooling roll 40 is more preferably 30 to 90°C.

[0053] The F polymer (film 1) after being separated from the first cooling roll 30 may be subjected to a surface treatment capable of introducing adhesive functional groups into its surface. Examples of such surface treatments include discharge treatments such as corona discharge treatment and plasma treatment, plasma graft polymerization treatment, light irradiation treatments such as electron beam irradiation and excimer UV light irradiation, itro treatment using a flame, and wet etching treatment using metallic sodium. This surface treatment introduces polar functional groups such as hydroxyl groups, carbonyl groups, and carboxy groups onto the surface of film 1, thereby improving adhesion to other surfaces.

[0054] The laminate of the present invention (hereinafter also referred to as "the laminate") will be described below. This laminate is a laminate in which an F polymer layer (a layer made of the film of the present invention) and a substrate layer are laminated in this order. This laminate is preferably obtained by laminating the film of the present invention and a film-like or sheet-like substrate other than the film of the present invention by a roll-to-roll method, for example, at a melting temperature of the F polymer to 400°C, or by overlapping and then heat pressing at a melting temperature of the F polymer to 400°C.

[0055] The material of the substrate layer in the present laminate includes metals and resins. Examples of the resin include thermoplastic resins, non-thermofusible resins, uncured curable resins, cured curable resins, etc. In particular, metals and heat-resistant resins are preferred. The substrate layer in the present laminate is preferably a layer formed from a film-like or sheet-like substrate, and the film-like or sheet-like substrate is preferably a metal foil or a heat-resistant resin film. The substrate layer in the present laminate may also be a resin layer or a metal layer formed on the surface of the film of the present invention by means of coating, plating or the like.

[0056] When the substrate layer in the present laminate is a layer formed from a metal foil, the ten-point average roughness of the surface of the metal foil is preferably 0.01 μm or more and 0.5 μm or less. In this case, the film of the present invention and the metal foil are more likely to adhere firmly to each other. Therefore, the laminate having the film of the present invention with high thickness accuracy and the printed circuit board obtained by processing the same are more likely to exhibit remarkable electrical properties. Specifically, when the substrate layer in the present laminate is made of a metal foil, the dielectric loss tangent of the F polymer layer of the present laminate at a frequency of 10 GHz is preferably 0.0001 to 0.0020.

[0057] Examples of the material for the metal foil include iron, copper, nickel, titanium, aluminum, and alloys thereof (stainless steel, nickel 42 alloy, etc.) As the metal foil, rolled copper foil and electrolytic copper foil are preferred. The surface of the metal foil may be subjected to an anti-rust treatment (formation of an oxide film such as chromate). The surface of the metal foil may also be treated with a silane coupling agent. The treatment area may be a part of the surface of the metal foil or the entire surface. The thickness of the metal foil is preferably 0.1 to 20 μm, and more preferably 0.5 to 10 μm.

[0058] The metal foil may be a carrier-attached metal foil containing two or more layers of metal foil. The carrier-attached metal foil may be a carrier-attached copper foil consisting of a carrier copper foil (thickness: 10 to 35 μm) and an ultra-thin copper foil (thickness: 2 to 5 μm) laminated on the carrier copper foil via a release layer. By using such a carrier-attached copper foil, it is possible to form a fine pattern by a modified semi-additive (MSAP) process. As the release layer, a metal layer containing nickel or chromium, and a multi-layer metal layer in which this metal layer is laminated are preferable. A specific example of the metal foil with a carrier is "FUTF-5DAF-2" manufactured by Fukuda Metal Foil & Powder Co., Ltd.

[0059] The substrate layer of the laminate may be a metal layer formed by a vapor phase deposition method and a plating method. The metal layer can be formed, for example, by forming a metal seed layer on the surface of the film of the present invention by a sputtering method or an electroless plating method, and then growing a metal from the seed layer by an electrolytic plating method. Before forming the seed layer, the surface of the film of the present invention may be surface-treated. Examples of the surface treatment method include annealing treatment, corona treatment, plasma treatment, ozone treatment, excimer treatment, and silane coupling treatment. Metals that can be plated by electroless plating include copper and nickel. Metals in the seed layer include copper, nickel, chromium, nichrome alloys, titanium alloys, and the like. An example of the metal to be plated by electrolytic plating is copper.

[0060] When the substrate layer in the present laminate is a layer of a heat-resistant resin film, the film contains one or more types of heat-resistant resin and may be a single-layer film or a multi-layer film. The heat-resistant resin film may have glass fibers, carbon fibers, or the like embedded therein. When the substrate layer is a layer of a heat-resistant resin film, the laminate is preferably a laminate having a structure in which the film of the present invention is laminated on both sides of the substrate layer. In this case, since the film of the present invention is laminated on both sides of the heat-resistant resin film, the linear expansion coefficient of the laminate is significantly reduced, and warping is unlikely to occur. Examples of the heat-resistant resin include polyimide, polyarylate, polysulfone, polyarylsulfone, aromatic polyamide, aromatic polyetheramide, polyphenylene sulfide, polyaryletherketone, polyamideimide, liquid crystal polyester, and liquid crystal polyesteramide, and polyimide (particularly, aromatic polyimide) is preferred.

[0061] In the present laminate, which is a heat-resistant resin film having the film of the present invention on both sides, the thickness (total thickness) is preferably 220 μm or more, more preferably 250 μm or more. The thickness is preferably 500 μm or less. In such a configuration, the ratio of the total thickness of the two F polymer layers to the thickness of the heat-resistant resin film is more preferably 0.8 or more. The ratio is preferably 5 or less. In this case, the properties of the heat-resistant resin film (high yield strength, low plastic deformation property) and the properties of the F polymer layer (low water absorbency) are exhibited in a well-balanced manner.

[0062] Specific examples of the present laminate include a metal-clad laminate having a metal foil and an F polymer layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and an F polymer layer on both surfaces of the polyimide film. A preferred embodiment of the present laminate in which the base layer is a heat-resistant resin film is a three-layer film in which the heat-resistant resin film is a polyimide film having a thickness of 20 to 100 μm, and the film of the present invention, a polyimide film, and a film of the present invention are laminated in this order in direct contact with each other. In this embodiment, the thicknesses of the two films of the present invention are the same, and preferably 100 to 200 μm. The ratio of the total thickness of the two films of the present invention to the thickness of the polyimide film is preferably 0.5 to 5. The laminate of this embodiment is most likely to exhibit the effects of the laminate described above.

[0063] Here, the outermost surface of the present laminate (the surface of the F polymer layer opposite the substrate layer) may be further surface-treated in order to further improve its linear expansion properties and adhesiveness. Examples of the surface treatment method include annealing treatment, corona treatment, plasma treatment, ozone treatment, excimer treatment, and silane coupling treatment. The annealing conditions are preferably a temperature of 120 to 180° C., a pressure of 0.005 to 0.015 MPa, and a time of 30 to 120 minutes. Examples of gases used in the plasma treatment include oxygen gas, nitrogen gas, rare gas (argon, etc.), hydrogen gas, ammonia gas, and vinyl acetate. These gases may be used alone or in combination of two or more.

[0064] The metal foil of this laminate (metal foil with F polymer layer) in which the base layer is metal foil is etched to form a transmission circuit, thereby obtaining a printed circuit board. Specifically, the printed circuit board can be manufactured by a method of processing the metal foil into a desired transmission circuit by etching the metal foil, or by a method of processing the metal foil into a desired transmission circuit by electrolytic plating (semi-additive method (SAP method), MSAP method, etc.). A printed circuit board manufactured from the metal foil with an F polymer layer has a transmission circuit formed from the metal foil and an F polymer layer in this order. Specific examples of the configuration of a printed circuit board include transmission circuit / F polymer layer / prepreg layer and transmission circuit / F polymer layer / prepreg layer / F polymer layer / transmission circuit. In the manufacture of such a printed circuit board, an interlayer insulating film may be formed on the transmission circuit, and a coverlay film may be laminated on the transmission circuit. These interlayer insulating films and coverlay films may be formed from the film of the present invention.

[0065] The film of the present invention, the production method thereof, and the laminate of the present invention have been described above, but the present invention is not limited to the configurations of the above-mentioned embodiments. For example, in the film of the present invention and the laminate of the present invention, any other structure may be added to the above-mentioned structure, or any structure that exerts the same function may be substituted. Furthermore, the manufacturing method of the present invention may have any other steps added to the configuration of the above embodiment, or may be substituted with any other steps that produce the same effect. EXAMPLES

[0066] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Details of each component are shown below. [F Polymer] F polymer 1: a polymer having an acid anhydride group, containing 98.0 mol%, 0.1 mol%, and 1.9 mol% of TFE units, NAH units, and PPVE units, in that order (melting temperature 300°C) F polymer 2: a polymer having no functional group, containing 98.0 mol% and 2.0 mol% of TFE units and PPVE units, in that order (melting temperature 300°C) In addition, F polymer 1 has a carbonyl group-containing group with a main chain carbon number of 1 × 10 6 Each polymer has 1000 molecules, and F polymer 2 has 40 molecules. [pellet] Pellet 1: Pellet of F polymer 1 (diameter: 2.2 mm) [Haze measurement] The haze (cloudiness) of the films obtained in each of the Examples was measured in accordance with JIS K 7136 using NDH5000 (manufactured by Nippon Denshoku Industries Co., Ltd.). [Thermal expansion / contraction rate] According to JIS K7133:1999, the film was cut into a size of 120 mm x 120 mm, 100 mm marks were drawn in the machine direction (MD) and transverse direction (TD) of the film, and the length of the marks was measured. The film was placed in an oven at 180°C for 30 minutes, and then naturally cooled to 25°C. The length of the marks was measured again, and the expansion rate was calculated according to the following formula. Formula: {(length of gauge before heating)-(length of gauge after heating)} / (length of gauge before heating) x 100 [Film appearance] The film was placed on a smooth glass surface, and the presence or absence of warping (waviness) was confirmed and evaluated according to the following criteria. ◯: No warping (waviness) observed. ×: Warping (waviness) is observed.

[0067] [Example 1] (1) Film manufacturing After the F polymer 1 was put into an extruder at 350 ° C, it was extruded from a T-die with a width of 1600 mm to a thickness of 125 μm. The die temperature was 350 ° C, and the die lip temperature was 370 ° C. The extruded molten F polymer 1 was sandwiched between the first cooling roll 30 at 200 ° C by the quenching roll 301, which is a metal elastic roll controlled at 90 ° C., and then, toward the first cooling roll, an air knife (height 50 mm) installed in a tangent line contacting the first cooling roll and perpendicularly blowing a slit-shaped air flow at 200 ° C. uniformly in a line in the width direction of the first cooling roll 30 at a wind speed of 15 m / sec, and pressed against the first cooling roll 30, and then passed through the second cooling roll 40 at 90 ° C., and was taken up by the winding rolls 61 and 62 heated to 90 ° C. The haze of the obtained film (hereinafter referred to as PFA film 1) was 3%, and the thermal expansion rate after heating at 180° C. for 30 minutes was 0.2% in MD and −0.3% in TD. A hopper was connected to the front of the kneading section of the extruder, and F polymer 1 was added by feeding pellets 1 into the hopper, reducing the pressure in the hopper to 100 Pa or less, and heating the hopper, and adjusting the temperature of the F polymer at the connection section to 180° C. In addition, the molten F polymer 1 extruded from the T-die was heated to 320° C. with a non-contact heater before contacting the quench roll and the first roll. (2) Manufacturing and evaluation of antenna substrate A nickel-chromium alloy layer was formed on the PFA film 1 by sputtering a nickel-chromium alloy to a thickness of 10 nm using a roll-to-roll method, and then a copper layer was formed on the nickel-chromium alloy layer by sputtering copper to a thickness of 200 nm. Furthermore, a dry film resist was roll-laminated on the copper layer at 90°C, and then exposed and developed so that the mesh width was 6 μm. The mesh portion was plated to a thickness of 6 μm by copper sulfate electrolytic copper plating. Thereafter, the dry film resist was peeled off, and then the copper layer and the nickel-chromium alloy layer formed by sputtering were removed by etching to obtain an antenna substrate. The electrical resistance of the obtained antenna substrate was measured, and the electrical continuity was evaluated as conductive (◯) / non-conductive (×). In addition, the haze after forming the mesh antenna on the antenna substrate was measured by the above-mentioned method. Table 1 shows the film manufacturing conditions, film characteristics, and performance evaluation results as an antenna.

[0068] [Example 2] A film (PFA film 2) was produced in the same manner as in (1) of Example 1, except that F polymer 2 was used instead of F polymer 1, and air was not blown onto the molten F polymer 2 with an air knife on the first cooling roll. An antenna substrate and an antenna were produced using the obtained PFA film 2 in the same manner as in (2) of Example 1, and evaluated in the same manner. The film production conditions, film properties, and performance evaluation results as an antenna are shown in Table 1.

[0069] [Example 3] F polymer 1 was extruded from a T-die to a thickness of 125 μm, and the film was taken up via the first cooling roll without using the quenching roll 301 (i.e., without sandwiching between the quenching roll 301 and the first cooling roll 30), and without blowing air onto the molten F polymer 1 with an air knife on the first cooling roll, a film was produced in the same manner as in (1) of Example 1 (PFA film 3). Using the obtained PFA film 3, an antenna substrate and an antenna were produced in the same manner as in (2) of Example 1, and evaluated in the same manner. The film production conditions and film properties of the obtained PFA film 3, as well as the evaluation results of its performance as an antenna, are shown in Table 1. PFA film 3 had poor adhesion to the first cooling roll, and had "air marks" caused by air getting between the film and the first cooling roll, and its appearance was poor.

[0070] [Table 1] [Industrial Applicability]

[0071] The film of the present invention is useful as an antenna cover material because it is transparent and has excellent dimensional stability. In addition, the film of the present invention can be easily processed into a metal laminate (metal foil coated with resin), and the processed products obtained can be applied to various fields, including flexible device equipment such as transparent flexible printed circuit boards, antenna parts, printed circuit boards, sports equipment, and food industry products, as well as wearable equipment and medical equipment that place importance on design. The entire contents of the specification, claims, abstract and drawings of Japanese Patent Application No. 2020-062167, filed on March 31, 2020, are hereby incorporated by reference as the disclosure of the specification of the present invention. [Explanation of symbols]

[0072] Reference Signs List 1...film, 10,101...manufacturing device, 20...T-die, 21...lip, 30...first cooling roll, 301...quenching roll, 40...second cooling roll, 50...take-up roll, 61,62...conveyor roll, 70...air knife, 80...heater, t...thickness, S...circumferential speed, 11...extrusion molding device, 2...hopper, 21...first stage, 211...heater, 212...connection, P1...pump, 22...second stage, 221...heater, 222...connection, P2...pump, 3...kneading section, 31...cylinder, 311...tip opening, 32...screw, 33...gearbox, 331...rotating shaft, 34...motor, 341...rotating shaft, 35...heater, 5...T-die, 6...static mixer, L...total length, D...diameter

Claims

1. The extrusion-molded film is made of a tetrafluoroethylene-based polymer, and has a thickness of 100 to 200 μm, a haze of 8% or less, and a thermal expansion rate of −1 to +1% in both the machine direction and the width direction of the film after heating at 180° C. for 30 minutes.

2. 2. The film of claim 1, wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer that includes units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether).

3. The film according to claim 1 or 2, wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether) and having a polar functional group, or a tetrafluoroethylene-based polymer containing 2.0 to 5.0 mol % of units based on perfluoro(alkyl vinyl ether) relative to all units and having no polar functional group.

4. The film according to any one of claims 1 to 3, wherein the melting temperature of the tetrafluoroethylene-based polymer is 260 to 320°C.

5. A method for producing the film according to any one of claims 1 to 4 by a T-die casting method, comprising the steps of discharging the tetrafluoroethylene-based polymer in a molten state from a die to be extruded, and then sandwiching the film between two temperature-controlled rolls to cool it.

6. The method according to claim 5, wherein one of the two temperature-controlled rolls has a temperature of 150 to 250°C, and the other has a temperature of 80 to 150°C.

7. 7. The method according to claim 5 or 6, further comprising the steps of: feeding pellets of a tetrafluoroethylene-based polymer having a melting temperature of 260 to 320°C into the hopper; and discharging the molten mixture melted and kneaded in the kneading section from a T-die to produce a film; adjusting the temperature of the pellets at a connecting portion of the hopper with the kneading section to a range of (the melting temperature - 200) to (the melting temperature - 100)°C, and then supplying the pellets to the kneading section.

8. The method according to any one of claims 5 to 7, wherein the pellets have a diameter of 1.0 to 4.0 mm.

9. The manufacturing method according to any one of claims 5 to 8, wherein the hopper is a multi-stage hopper having a first stage and a second stage arranged on the kneading section side of the first stage.

10. The method according to any one of claims 5 to 9, wherein a pressure in a step of the hopper closest to the kneading section is 1000 Pa or less.

11. The manufacturing method according to any one of claims 5 to 10, wherein the extrusion molding apparatus comprises a T-die connected to the axial side of the kneading section opposite to the hopper, and a static mixer provided between the kneading section and the T-die.

12. The manufacturing method according to any one of claims 5 to 11, further comprising the steps of discharging the tetrafluoroethylene-based polymer in a molten state from a T-die and heating the molten tetrafluoroethylene-based polymer in a non-contact heating section before the polymer comes into contact with a first cooling roll.

13. The method according to claim 12, wherein the difference between the temperature of the tetrafluoroethylene-based polymer in the T-die and the temperature of the first chill roll is 250°C or less.

14. The method according to claim 12 or 13, wherein an absolute value of a difference between a temperature of the tetrafluoroethylene-based polymer in the T-die and a temperature of the non-contact heating part is 70° C. or less.

15. A laminate comprising a layer made of the film according to any one of claims 1 to 4 and a substrate layer made of a substrate other than the film.

Citation Information

Patent Citations

  • Mold release film

    JP2013147026A

  • Film, laminated film, and laminated molded article

    JP2017206671A

  • Molded body for biodiesel fuel

    US20110014478A1

  • Material for printed circuit board, metal laminate, methods for producing them, and method for producing printed circuit board

    US20180050516A1

  • Laminated substrate, and method for producing its formed product

    US20180154614A1